Effect of genetic variants associated with plasma homocysteine levels on stroke risk - Cotlarciuc, Ioana (2014)
BACKGROUND AND PURPOSE: Elevated homocysteine (tHcy) levels are known to be associated with increased risk of ischemic stroke (IS). Given that both tHcy and IS are heritable traits, we investigated a potential genetic relationship between homocysteine levels and stroke risk by assessing 18 polymorphisms previously associated with tHcy levels for their association with IS and its subtypes. METHODS: Previous meta-analysis results from an international stroke collaborative network, METASTROKE, were utilized to assess association of the 18 tHcy associated SNPs in 12,389 IS cases and 62,004 controls. We also investigated the associations in regions located within 50kb from the 18 tHcy related SNPs, and the association of a genetic risk score including the 18 SNPs. RESULTS: One SNP located in the RASIP1 gene and a cluster of three SNPs located at and near SLC17A3 were significantly associated with IS (P<0.0003) after correcting for multiple testing. For stroke subtypes, the sentinel SNP located upstream of MUT was significantly associated with SVD (small vessel disease) (P=0.0022), while one SNP located in MTHFR was significantly associated with LVD (large vessel disease) (P=0.00019). A genetic risk score including the 18 SNPs did not show significant association with IS or its subtypes. CONCLUSIONS: This study found several potential associations with IS and its subtypes: an association of an MUT variant with SVD, an MTHFR variant with LVD, and associations of RASIP1 and SLC17A3 variants with overall IS.